Hexachlorophene as a topically applied chemical for prophylaxis against Schistosoma mansoni infections in mice - Marie M. Grenan; Lyfford K. Greene; David E. Davidson Jr.; Douglas H. Jones; Tommy R. Shedd; Gregory Hiestand (Revista do Instituto de Medicina Tropical de São Paulo, 1985)
Treatment of mouse tail skins with hexachlorophene (1.25% w/v) in absolute methanol or 70% isopropanol suppressed Schistosoma mansoni infections by more than 95% even when the application was performed up to three days prior to exposure to cercarial suspensions by tail immersion. Treatment with concentrations of 0.313% or higher one day prior to exposure provided at least 98% protection when the treated surface was not subjected to water washes of greater duration than 1/2 hour. Tail immersion application of 1.25% hexachlorophene one day prior to exposure still provided 87-92% protection after 3 hours water wash. Wipe application of 1.25% hexachlorophene three days prior to exposure still provided 93% protection following 3 hours water wash. High cercarial recoveries from exposure tubes at the end of exposure periods indicated high antipenetrant activity for hexachlorophene. Sufficient hexachlorophene leached from treated tail skins into the surrounding water to affect subsequently added cercariae so that they were no longer infective to untreated mice.